Comparative Numerical Analysis on Vertical Wind Turbine Rotor Pattern of Bach and Benesh Type - Fanel Dorel Scheaua (Energies, 2020)
In this work, 3D models in classic configuration of Bach and Benesh rotor type, as well as models with modified blade pattern geometry were analyzed from the air circulation point of view inside the rotor enclosure in order to identify the operating parameters differences according to rotor geometric modified configuration. Constructive design aspects are presented, as well as results obtained from the virtual model analysis in terms of circulation velocity and pressure values which enhance rotor operation related to torque and power coefficients. The rotors design pattern is made according to previous results obtained by different researchers who have performed numerical analysis on virtual models and tests on the experimental rotor models using the wind tunnel. The constructive solutions are describing two-bladed rotor models, in four new designed constructive variants and analyzed using ANSYS CFX. The air velocity specific values, static and total pressure recorded at the rotor blade level are highlighted, that influence the obtaining of rotor shaft torque and power. Also torque coefficient (CT) and power coefficient (CP) values according with specific values of tip speed ratio (TSR) are presented for each analyzed case. The analysis results show higher power coefficient values for analyzed Bach V2 and Benesh V2 rotor modified models compared to the classic Bach and Benesh models for 0.3 TSR of 0.11–012 CP, 0.4 TSR of 0.18 CP (Benesh V2 model) and 0.27 CP at 0.6 TSR (Bach V2). The resulted values confirm that Benesh V2 model offers higher CP up to 5% at TSR 0.3, 2% at TSR 0.6 and 3% at TSR 0.4 compared to the Benesh classical model. The Bach V2 model offers 4% higher CP compared to the classic Bach model at TSR 0.6. Based on these results it is intended the further analytical and experimental research in order to obtain optimal rotor pattern.